Service Quality Based Analysis : Case of Housekeeping Attendant, Segara Village Hotel - Ni Made Ayu Sulasmini; I Gede Gio Pana Saputra (Journal of Business on Hospitality and Tourism, 2015)
Quality of service is any activity carried out by the company or hotel in order to meet consumer expectations. The dimensions of the service quality are Tangible, Reliability, Responsiveness, Assurance and Empathy. Various efforts need to be considered by the hotel in order to satisfy the guests. So is the case with Segara Village Hotel which is a four-star hotel in Sanur. This study aims to determine the quality of service of room attendants at Segara Village Hotel, using the techniques of qualitative-quantitative descriptive analysis. Respondents in this study were guests at Segara Village Hotel as many as 50 people. Data obtained by questionnaires that measured using a Likert scale. Data were analyzed using analysis techniques and performance level of importance, and the Cartesian diagram. It was found that the factors are a top priority (considered important by guests, but the implementation is felt still less) is the appearance of room attendant, accuracy, reliability, timeliness in cleaning room, the provision of information to the guests, room attendant accuracy, and understanding of what is desired by guests.